The Combination of Artificial Intelligence and Extended Reality: A Systematic Review - Reiners, Dirk; Davahli, Mohammad Reza; Karwowski, Waldemar; Cruz-Neira, Carolina (Frontiers in Virtual Reality, 2021)
Artificial intelligence (AI) and extended reality (XR) differ in their origin and primary objectives. However, their combination is emerging as a powerful tool for addressing prominent AI and XR challenges and opportunities for cross-development. To investigate the AI-XR synergy, we mapped and analyzed published articles through a multi-stage screening strategy. We identified the main applications of the AI-XR combination, including autonomous cars, robotics, military, medical training, cancer diagnosis, entertainment and gaming applications, advanced visualization methods, smart homes, affective computing, and driver education and training. In addition, we found that the primary motivation for developing the AI-XR applications include (1) training AI models, (2) conferring intelligence on XR, and (3) interpreting XR dynamics. Finally, our results highlight the advancements and future perspectives of the AI-XR synergy.